Comportamientos relacionados con las enfermedades crónicas no transmisibles en estudiantes universitarios - Lerma Castaño, Piedad Rocío; Jaimes Guerrero, Carlos Alberto; Mantilla Toloza, Sonia Carolina; Castro Betancourt, Dolly; Tamayo Perdomo, Gladys; Antolínez Álvarez, Martha Florelia; Alvarado Rozo, Omar Alberto (Revista Médica de Risaralda, 2021)
Introduction: The scientific literature has reported the trend of the impact of non- communicable diseases on public health, and therefore, the investment of resources that interfere in the development of a country. Objective: To identify the presence of specific behaviors associated with the development of chronic non-communicable diseases in university students, since they are a susceptible population to the modification of these tendencies. Materials and methods: This cross-sectional descriptive study was carried out on a 375 university students’ sample. The stepwise method was applied to identify risk factors associated with the development of chronic non-communicable diseases. Descriptive statistics and bivariate analysis were used to determine possible relationships between the variables studied. Results: The prevalence of tobacco use was 7.5%, frequent alcohol consumption was 91.5%, fruit intake was 96.3%, and vegetable intake was 95%. Additionally, only 48% of the sample practiced intense physical activity. Also, a relationship among the male sex, with the consumption of tobacco and the practice of low physical activity was found. Conclusions: Behaviors associated with chronic non-communicable diseases such as alcohol and tobacco consumption were identified in university students.